The Map of The Religious Elite Conflict and Resolution Effort - Lathifatul Izzah; Misyrah Ahmadi; Kurniati Kurniati (IAIN Ponorogo, 2021)
Conflict can occur anywhere and anytime, even in a society that looks homogeneous and religious. This paper aims to describe, analyze, and interpret the causes of the operation of the religious elite conflict in Mlangi and the resolution efforts for this conflict. These objectives can be achieved by using a qualitative approach with the type of case study research designed in the form of a single case. The data collection techniques can be done by observation, interviews, and documentation which makes the author himself a research instrument. The results obtained from these achievements are as follows: conflicts of religious elites can occur because there are symbolic buildings that are glorified by the local community, struggle for social position between jero and jobo communities, changes in regional administration and social structures, intersections between religion, economy and political elites local, struggling for access to information, resources and sources of funds, differences in livelihoods, and the emergence of negotiations on religious and cultural values. Some of the causes of the conflict can be eliminated by fading the building of symbols that reinforce social position and status, allowing mixed marriages, creating awareness of equality of origin or descent, needing government intervention to find a middle way for the conflict, creating common enemies and independence.